ANALYSIS OF THE ROLE OF STAKEHOLDERS AND THE IMPACT OF VILLAGE SUSPENSION BRIDGE CONSTRUCTION IN POVERTY ALLEVIATION IN WEST JAVA - Kusumawati, Riny (LPPM Univ. Ibn Khaldun Bogor, 2024)
The village suspension bridge (heart) is a bridge built by the West Java Government in the field of infrastructure and functions to connect the two ends of the road that are cut off by obstacles, rivers and waterways in rural areas. The benefits: easy access to education and the economy, accelerating disaster management, poverty alleviation and developing rural tourism potential. The goal is: realizing development, government administration and equity/improvement of village capabilities in poverty alleviation. Research problems: (1) What is the role of stakeholders in the construction of village suspension bridges, (2) What is the impact of the construction of village suspension bridges on improving community welfare and poverty alleviation in West Java. The objectives of the study: (1) Analyze the role of stakeholders in the construction of village suspension bridges, and (2) Analyze the impact of village suspension bridge construction on improving community welfare and poverty alleviation in West Java. Research methods used: descriptive research method with a qualitative approach and primary and secondary data collection with purposive sampling method and Focus Group Discussion. The results of the study will show that the impact of development in terms of infrastructure, economy, social and environment has increased/has not increased. In addition, the role of stakeholders in development is also important so that development can be maximized, and obstacles in development are also identified, especially in terms of economy and community mobility. If the obstacles are followed up, efforts to improve community welfare and poverty alleviation can be realized immediately.